Association of Blood Transfusion and Retinopathy of Prematurity in Preterm Neonate - Fatema Akter Joly; Md. Mahbubul Hoque; Abu Naser Md. Faiaz; Md Shafiul Alam Quarashi (Saudi Journal of Medicine, 2026)
Background: Retinopathy of prematurity (ROP) is a vaso-proliferative disorder of the immature retina and a leading cause of preventable childhood blindness. Multiple risk factors have been implicated in its development, including oxygen therapy, sepsis and blood transfusion. Objective: This study was conducted to determine the association between blood transfusion and ROP among preterm neonates and to assess the effect of early erythropoietin (EPO) administration on anemia correction and transfusion requirement. Methods: This randomized controlled trial was conducted in the Special Care Baby Unit (SCABU) and Neonatal Intensive Care Unit (NICU) of Dhaka Shishu (Children) Hospital from July 2018 to June 2020. A total of 60 preterm low-birth-weight neonates (